PENCIPTAAN BUKU ILUSTRASI KAIN SASIRANGAN SEBAGAI UPAYA PROMOSI SENI BUDAYA BANJARMASIN KEPADA REMAJA - Wijaya, Tonny Aries; Fianto, Achmad Yanu Alif; Hidayat, Wahyu (Jurnal Art Nouveau, 2015)
Abstract: The goal of the design creation illustrated book Sasirangan fabrics are promotional efforts, provide more information about the fabrics Sasirangan for young people, especially teenagers get information about Cain Sasirangan and more loving culture of the region. The study was conducted using qualitative methods is by doing interviews, observation, documentation, and literature to obtain data that is used as a conception of making this illustrated book. The concept gained through data analysis is the specialty of Thousand Rivers. Descriptions of the concept of